ENT 600 : NPD : Smart Vending Machine (Vmac-Tech) / Nor Fatin Hanani Mohd Besri ... [et al.] - Mohd Besri, Nor Fatin Hanani; Mohd Amin, Atiqa Aisya Niesya; Nor Khairi Azmi, Azmi Zulhasni; Rosman, Muhammad Zulhilmi (2019)
The product to be develop is a smart vending machine (Vmac-Tech). Vending machines commonly used to disperse foods and beverages but nowadays many company also used this vending machine to sell their product such as rain coat even electronic items used this vending machine to promote their product. This vending machine are convenience for customer and available anywhere.